Analysis of an approach to pediatrics in the context of the pandemic by COVID-19 (Research, Society and Development, 2022)
Introduction: Pediatrics is the area of ​​medicine that takes care of a specific period of life, since the assistance that this area provides to human beings is from fertilization to puberty. Objectives: This study aims to approach pediatrics in the context of the COVID-19 pandemic. Methodology: 53 pediatricians from the Society of Pediatrics of Piauí (SOPEPI) were surveyed by completing an online form that was made available on the Google Forms platform. Results: With this study, it was possible to identify the modalities performed by pediatricians and realize that face-to-face care was still the most prevalent. In the pediatricians' perception, there was an increase in the stress level of them, children and those responsible for them, the latter being the most affected. Conclusion: The analyzed literature explains that this increase is caused by changes in the pandemic, including confinement, virtual classes, parents' home office and catastrophic news, in addition to the financial issue.